Perception of difficulties with vision-related activities of daily living among patients undergoing unilateral posterior capsulotomy - Firmani M. B. de Senne; Edméa R. Temporini; Carlos E. L. Arieta; Karla D. Pacheco (Clinics, 2010)
OBJECTIVES: To assess the influence of Nd:YAG (neodymium: yttrium-aluminum- garnet) laser unilateral posterior capsulotomy on visual acuity and patients' perception of difficulties with vision-related activities of daily life. METHODS: We conducted an interventional survey that included 48 patients between 40 and 80 years of age with uni- or bilateral pseudophakia, posterior capsule opacification, and visual acuity <0.30 (logMAR) in one eye who were seen at a Brazilian university hospital. All patients underwent posterior capsulotomy using an Nd:YAG laser. Before and after the intervention, patients were asked to complete a questionnaire that was developed in an exploratory study. RESULTS: Before posterior capsulotomy, the median visual acuity (logMAR) of the included patients was 0.52 (range 0.30-1.60). After posterior capsulotomy, the median visual acuity of the included patients improved to 0.10 (range 0.0-0.52). According to the subjects' perceptions, their ability to perform most of their daily life activities improved after the intervention (p<0.05). CONCLUSIONS: After patients underwent posterior capsulotomy with an Nd:YAG laser, a significant improvement in the visual acuity of the treated eye was observed. Additionally, subjects felt that they experienced less difficulty performing most of their vision-dependent activities of daily living.